2022
DOI: 10.1016/j.omto.2021.12.002
|View full text |Cite
|
Sign up to set email alerts
|

SNX5 suppresses clear cell renal cell carcinoma progression by inducing CD44 internalization and epithelial-to-mesenchymal transition

Abstract: Aberrant expression of SNX5 can contribute to tumorigenesis, invasion, and metastasis of several human cancers. However, the clinicopathological and biological significance of SNX5 in clear cell renal cell carcinoma (ccRCC) remain unclear. In this study, we found that SNX5 expression was downregulated and negatively correlated with tumor size, American Joint Committee on Cancer stage, tumor thrombus of inferior vena cava, and poor prognosis in human ccRCC. Ectopic expression of SNX5 inhibited ccRCC cell prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Our results suggest that MXI1 promotes ccRCC cell growth by activating the transcription of hexokinase 2 (HK2). KLF9 is a Krupple-like transcription factor (KLF) and was shown to transactivate KCNQ1 110 and SNX5 109 , inhibiting ccRCC cell proliferation. In snRNA-seq data, KLF9 is not significantly differentially expressed between ccRCC tumor cells vs. PT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that MXI1 promotes ccRCC cell growth by activating the transcription of hexokinase 2 (HK2). KLF9 is a Krupple-like transcription factor (KLF) and was shown to transactivate KCNQ1 110 and SNX5 109 , inhibiting ccRCC cell proliferation. In snRNA-seq data, KLF9 is not significantly differentially expressed between ccRCC tumor cells vs. PT cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while previous studies relied on mutational and transcriptional similarities in support of PT as the cell of origin for ccRCC 44,[104][105][106] , we find strong epigenetic evidence suggesting this as well. When we compared chromatin accessibility patterns between tumor cells and normal PT cells, we uncovered many tumor-cell-specific TFs beyond the wellknown TF -HIF1A: MXI1, KLF9, RBPJ, and NFKB1/2 have been previously implicated in renal cancer tumorigenesis [107][108][109][110][111][112] ; and HSF2 and SREBF2 were linked to renal tubular cell injury 113,114 . As expected 115 , we observed a dozen genes upregulated in the glycolysis pathway in ccRCC cells compared to normal PT cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KLF9 functions as a haploinsufficient suppressor of colon tumorigenesis in Apc Min/+ mice by inhibition of interferon‐related signalling 37 . Zhou QQ et al reported that SNX5 could inhibit TGF‐β‐induced migration, invasion and EMT in clear cell renal cell carcinoma cells, and KLF9 directly binds to the SNX5 promoter and upregulates SNX5 transcription, thus inhibiting migration and EMT 38 . However, in oral squamous cell carcinoma (OSCC), Wang CY et al revealed a LINC00664/miR‐411‐5p/KLF9‐positive feedback loop that could promote migration, invasion and EMT of OSCC cells 39 .…”
Section: Discussionmentioning
confidence: 99%
“…SNX5 participates in caspase 9 mediated IGF2R retrieval mechanism ( 8 ) and forms a recycler complex with SNX4 and SNX17, which mediates the autophagosomal components recycling (ACR) process and helps the autophagosome membrane components on autophagy lysosomes to be recycled ( 9 ). In addition, SNX5 is also involved in the progression of cancers such as hepatocellular carcinoma ( 10 ) head and neck squamous cell carcinoma ( 11 ) and clear cell renal carcinoma ( 12 ).…”
Section: Snx5: a Protein Involved In Endosomesmentioning
confidence: 99%